Risk of Severe Maternal Morbidity or Death in Relation to Prenatal Biochemical Screening: Population-Based Cohort Study - Lentz, Eric J.M.; Park, Alison L.; Langlois, Alec W.R.; Huang, Tianhua; Meschino, Wendy S.; Ray, Joel G. (American Journal of Perinatology, 2019)
Objective This study aimed to examine whether prenatal biochemical screening analytes are associated with an increased risk of severe maternal morbidity (SMM) or maternal mortality.Study Design This population-based cohort study includes all women in Ontario, Canada, who underwent prenatal screening from 2001 to 2011. Increasing fifth percentiles of the multiple of the median (MoM) for alphafetoprotein (AFP), total human chorionic gonadotropin, unconjugated estriol (uE3), dimeric inhibin-A (DIA), and pregnancy-associated plasma protein A were evaluated. An abnormally high concentration (>95th percentile MoM) for each analyte, individually and combined, was also evaluated. The main outcome assessed was the adjusted relative risk (aRR) of SMM or maternal mortality from 20 weeks' gestation up to 26 weeks thereafter.Results Among 748,972 pregnancies, 11,177 resulted in SMM or maternal mortality (1.5%). Except for uE3, the aRR of SMM or maternal mortality increased in association with increasing fifth percentiles of the MoM for all analytes. AFP (aRR: 2.10; 95% confidence interval [CI]: 1.97–2.25) and DIA (aRR: 2.33; 95% CI: 1.98–2.74) > 95th versus ≤ 5th percentile of the MoM were especially associated with SMM or death.Conclusion Women with abnormally high concentrations of certain prenatal biochemical analytes may be at a higher risk of SMM or death in pregnancy or postpartum.
Keywords: prenatal biochemical screening; severe maternal morbidity; maternal mortality; maternal health